Complete Recovery of Visual Disorder Following Surgical Resection of Adenoid Cystic Carcinoma Arising in the Pterygopalatine Fossa: Case Report and Review of the Literature. Issue 22 (June 2015) - Du, Wei; Cui, Meng; Li, Peng; Wang, Jiheng; Luo, Ruihua; Qi, Jinxing; Zhao, Ming; Lou, Weihua
Abstract : Abstract: Adenoid cystic carcinoma (ACC) arising in the pterygopalatine fossa was rare, only 3 cases have been reported. In previous literature, few authors reported whether the visual deficit could be resolved following the resection of the tumor. One patient with visual dysfunction induced by ACC arising in the pterygopalatine fossa was reported. Complete visual recovery was achieved following the operation. And the patient was satisfied with the appearance and the functional results in the follow-up. Visual loss contributed by the tumor in the pterygopalatine fossa could recover in selected patients.